1994
DOI: 10.1007/bf01707664
|View full text |Cite
|
Sign up to set email alerts
|

Rapid fall in blood myoglobin in massive rhabdomyolysis and acute renal failure

Abstract: In patients with massive myoglobinaemia, the blood myoglobin rapidly fell independent of renal function or any therapeutic manipulation. The results indicate that extrarenal factors played a major role in disposing circulating myoglobin in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 7 publications
6
42
1
Order By: Relevance
“…The significant increases in serum and urine myoglobin and creatine kinase levels observed in the present study corresponded to those found in clinically severe cases of rhabdomyolysis [7], although the dose used was substantially lower than the muscle necrosis estimated to cause lethal rhabdomyolysis [8]. However, controversy exists on the role of myoglobin in the genesis of this syndrome [9].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The significant increases in serum and urine myoglobin and creatine kinase levels observed in the present study corresponded to those found in clinically severe cases of rhabdomyolysis [7], although the dose used was substantially lower than the muscle necrosis estimated to cause lethal rhabdomyolysis [8]. However, controversy exists on the role of myoglobin in the genesis of this syndrome [9].…”
Section: Discussionsupporting
confidence: 59%
“…The urinary myoglobin concentrations observed in the present animals corresponded to those reported in patients suffering from clinical rhabdomyolysis [7]. The decrease in the high serum myoglobin concentrations cannot be explained solely by increased urinary myoglobin output, other mechanisms may play a role, and may include renal metabolism [7], and myoglobin reabsorption in the glomeruli [24], as well as intestinal sequestration of myoglobin [25].…”
supporting
confidence: 72%
“…Pools do not equilibrate rapidly, such that effective blood purification will substantially reduce plasma myoglobin concentration [13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there is a very weak correlation between peak CK values and peak serum creatinine (1). Evidence that serum myoglobin falls quickly when muscle damage ceases, apparently independently of renal function, suggests a potential clinical benefit from analyte measurement in cases where renal replacement therapy is involved (8). Whether myoglobin clearance could be used as an early indicator of renal outcome in muscle injury needs investigation (9).…”
mentioning
confidence: 99%